Marker-assisted identification of potential fertility restorers for the development of three-line hybrids in rice (Oryza sativa L.) - Majid, Asma; Parray, GA; Sofi, NR; Khan, Gazala H; Waza, Showkat A; Shikari, Asif B (ORYZA-An International Journal of Rice, 2020)
Rice being a staple food crop of Kashmir valley, the focus is on enhancement of yield in order to meet the needs of ever-growing population.Identification of new parental lines is crucial for developing ecology-specific hybrids with ideal agronomic performance. Exploitation of heterosis in the form of hybrid rice technology can be one of the approaches to increase productivity in this crop, especially exploiting diversity among japonica lines can serve as an excellent route.A number of CMS lines suitable formountainous areas of Kashmir have been developed, however, the availability of promising restorer lines remains to be the major limitation for utilization of these lines.Identification of potential restorers acts as the main limiting factor for hybrid development in the Kashmirvalley. Marker based screening for Rf3 and Rf4 fertility restorer genes can be helpful in rapid selection of restorer lines while dealing with the large quantity of genetic materials. In the present study, 100 rice germplasm were screened with the help of SSR markers, RM3148 and RM6100linked to Rf3 and Rf4 genes on chromosome 1 and 10, respectively. In total, 19 lines revealed the presence of both Rf3 and Rf4 genes. These lines amplified fertility restorer specific alleles for both the genes and may serve as potential restorers for obtaining heteroticrice hybrids. Further the germplasm lines were also evaluated for yield and quality traits.The present results would help in selection of suitable restorers along with preferred grain shape/size.